2012
DOI: 10.1007/s12369-012-0148-9
|View full text |Cite
|
Sign up to set email alerts
|

Telerobotic Pointing Gestures Shape Human Spatial Cognition

Abstract: This paper aimed to explore whether human beings can understand gestures produced by telepresence robots. If it were the case, they can derive meaning conveyed in telerobotic gestures when processing spatial information. We conducted two experiments over Skype in the present study. Participants were presented with a robotic interface that had arms, which were teleoperated by an experimenter. The robot could point to virtual locations that represented certain entities. In Experiment 1, the experimenter describe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…The participants also perceived both the embodied collaborator and the colleagues involved in the interaction as being more composed and involved when the embodied collaborator took a leadership role in the interaction. Spatial location recalling with a similar type of system as MeBot making use of Skype and arms was investigated in [99]. It was found that participants facing a system with verbal location descriptions accompanied by robotic pointing gestures remembered more locations in comparison with participants facing a system that only provided verbal descriptions when the locations were presented nonsequentially.…”
Section: Quality Of Communication Measuresmentioning
confidence: 99%
“…The participants also perceived both the embodied collaborator and the colleagues involved in the interaction as being more composed and involved when the embodied collaborator took a leadership role in the interaction. Spatial location recalling with a similar type of system as MeBot making use of Skype and arms was investigated in [99]. It was found that participants facing a system with verbal location descriptions accompanied by robotic pointing gestures remembered more locations in comparison with participants facing a system that only provided verbal descriptions when the locations were presented nonsequentially.…”
Section: Quality Of Communication Measuresmentioning
confidence: 99%
“…Next to social robots that assist people in medical situations [1][2][3], social robots can also help improve the user's spatial cognition through pointing gestures [4][5][6][7], improve the imitation skills of children with autism [8][9][10][11], or greet and communicate with people [12][13][14][15]. Therefore, we argue that one of the most important current challenges in research on social robotics is to develop social robots that can effectively influence human behavior or attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in human robot-interaction on how coverbal gestures affect comprehension has largely focused on pointing (deictic) gestures [5][23] [28], revealing that better understanding of relative locations of referents was achieved by supplementing speech information with deictic gestures. This provides some first evidence for speech and gesture integration.…”
Section: Gestures In Human-robot Interactionmentioning
confidence: 99%